The impact of solvent type and mixing ratios of solvents on the properties of polyurethane based electrospun nanofibers - PARS, ABDULKADİR; USTA, İSMAİL; YÜKSEK, METİN; ATAK, ONUR (ELSEVIER SCIENCE BV, 2015)
Electrospun Polyurethane based nanofibrous membranes were fabricated from the solutions prepared with various volume ratios of N,N-dimethylformamide (DMF) and Tetrahydrofuran (THF). Properties of the blended solutions were analyzed in terms of viscosity and conductivity. The morphology of nanofibrous membranes were observed by SEM analysis. Experimental results revealed that the morphologies of polyurethane nanofiber membranes have been changed significantly with the solvent selection and mixing ratios of the solvents for the electrospinning. Diameter of the nanofibers was recorded in the range between 277 nm and 556 nm, respectively. Tensile strength and elongation measurements confirmed that mechanical characteristics of the nanofibrous membranes were strongly influenced by the fiber morphology and the uniformity. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Polyurethane; Electrospinning; Nanofiber; Solvent; DMF; THF; FIBERS; MORPHOLOGY; POLYMER; MATS